Testing whether posttraumatic stress disorder and major depressive disorder are similar or unique constructs - Elhai, Jon D.; de Francisco Carvalho, Lucas; Miguel, Fabiano Koich; Palmieri, Patrick A.; Primi, Ricardo; Christopher Frueh, B. (Journal of anxiety disorders, 2011)
▶ Symptoms of MDD were endorsed less frequently than symptoms of PTSD—even for symptoms shared between the disorders. ▶ PTSD and MDD items primarily represent a single, underlying dimension. ▶ Removing shared PTSD-MDD symptoms and other dysphoria items, PTSD and MDD items continued to represent a single, underlying dimension. Posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) co-occur frequently, are highly correlated, and share three symptoms in common. In the present paper, the authors tested whether PTSD and MDD are similar or unique constructs by examining their symptoms using Rasch modeling. Data were used from the 766 trauma-exposed subjects in the National Comorbidity Survey-Replication (conducted in the early 2000s) with PTSD and MDD symptom ratings. Results demonstrate that MDD symptoms were less frequently endorsed than PTSD symptoms—even for the three symptoms shared between the disorders. PTSD and MDD items represented a single, underlying dimension, although modest support was found for a secondary sub-factor. Removing their shared symptoms, and additional depression-related dysphoria symptoms, continued to result in a single underlying PTSD-MDD symptom dimension. Results raise further questions about PTSD's distinctiveness from MDD, and the causes of their comorbidity.